Language proficiency differences in second language learning anxiety - Nur Atikah Binti Noor Rashid; Asnadia Binti Alias (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
In general, the objective of learning English language in Malaysian education system is to ensure the students can use English in their daily basis, to further study and for the workplace. The main purpose of English course in Polytechnics is to ensure the students are able to communicate effectively and confidently. Therefore, the students should be able to understand the language and use it with confident in their daily lives and for their future employment. However, most of the students are reluctant to communicate in English and many of them prefer to withdraw from participating in any English language activities. The reason for this issue might be due to the feeling of anxiety in learning the second language. Hence, this study aimed to investigate the language proficiency differences between above average and below average students with respect to language learning anxiety. There were 96 semester three students from Civil Engineering Department, Politeknik Sultan Mizan Zainal Abidin participated in this study. SPSS version 22 has been used to analyses collected data consists of a 33 item questionnaire of Foreign Language Classroom Anxiety Scale (FLCAS). The t-test has been used to determine if there was a significant difference between above average and below average students in regard of language learning anxiety. The study revealed that below average students were more anxious than above average students for all types of anxiety. However, t-test demonstrated that there was no significant difference between language learning anxiety in regard of students’ level of proficiency. Thus, several implications have been suggested in this study to help the below average students to cater language learning anxiety. One of the examples is by conducting an English Camp for the targeted students serves as an effective method to cope language learning anxiety among below average students.